Large brown macula in a newborn - Santos Oliveira, Ana Gisela; Marques, João; Antunes, Joaquina; Maneira Sousa, Pedro; Cabral, Rita; Andrade, Isabel (BIRTH AND GROWTH MEDICAL JOURNAL, 2024)
The authors report the case of a male term newborn born after an uneventful monitored pregnancy. On physical examination, he presented with a light brown hyperpigmented homogeneous macule >15 cm in size compatible with a giant congenital melanocytic nevus (CMN). The boy was discharged with indication for Neonatology and Dermatology follow-up. Since then, he has shown adequate psychomotor growth and development and unremarkable neurologic examination and cranioencephalic magnetic resonance imaging. CMN is a benign proliferation of melanocytes forming theca/nests in the dermal-epidermal junction and/or dermis. It may be present at birth or develop during the first two years of life in any body area. CMN can be classified as small, medium, large, giant, or multiple. Giant CMN is rare and is a risk factor for melanoma. Management of CMN should be based on age, nevus size, and other factors. Because of the potential for malignancy, giant CMN requires clinical surveillance with neurodevelopmental monitoring and regular dermoscopy, as well as early surgical management of suspicious lesions.